133k views
7 votes
Can any kind soul help me ASAP!​

Can any kind soul help me ASAP!​-example-1

1 Answer

4 votes

Answer:
(-2p^2+10p-8)/(p^2-4)

This can be written as (-2p^2+10p-8)/(p^2-4) on a keyboard.

=======================================================

Work Shown:


(2p)/(p^2-4) + (4-2p)/(p+2)\\\\\\(2p)/((p+2)(p-2)) + (4-2p)/(p+2)\\\\\\(2p)/((p+2)(p-2)) + ((4-2p)(p-2))/((p+2)(p-2))\\\\\\(2p+(4-2p)(p-2))/((p+2)(p-2))\\\\\\(2p-2p^2+8p-8)/(p^2-4)\\\\\\(-2p^2+10p-8)/(p^2-4)\\\\\\

---------------------

Explanations:

  • In step 2, I factored p^2-4 using the difference of squares rule.
  • In step 3, I multiplied top and bottom by (p-2) so that the second fraction has a denominator of (p+2)(p-2). We can only add fractions that have the same denominator.
  • In step 5, I used the FOIL rule to expand (4-2p)(p-2) into -2p^2+10p-8. You can use the distribution rule or the box method as alternatives.
User Chub
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.